Impediments to the application of foreign law before the national judiciary in civil disputes - جلب طارق; غسان علي (Latakia University Journal - Economic and Legal Sciences Series, 2022)
Most of the legislations in the world have required the judge to refrain from applying foreign law if it violates public order or if it is proven that he has jurisdiction by cheating towards the law as general reasons for excluding foreign law, including the Syrian legislator, which states that a contract that violates public order and morals is an absolute void contract, as Public order is a set of rules necessary for social life, and the concept of public order or its idea refers to the theory of the state, and we studied in this research the definition of public order and the effects that result from pushing public order and how the theory of fraud towards the law arose and the conditions for pushing fraud towards law and law The effect of fraudulent payment towards the law We concluded that the contract concluded under a foreign law and in violation of public order or fraud is considered an absolute nullity, and therefore any of the contracting parties has the right to raise it, and the court also has the right to raise it on its own, and this is what is stipulated in Article / 136/ of the Syrian Civil Code By saying: If the subject of the obligation is contrary to public order or morals, the contract is void.” Likewise, Article / 137/ which states: “If the obligation has no cause, or if its cause is contrary to public order or morals; The contract was void." .